Kyrgyz Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper examines figures related to the key policy areas for the Kyrgyz Republic. Specifically, the paper studies the sources of growth, the cost competitiveness of export, and trade restrictions in the region, which are all linked to the achievement of the growth and poverty reduction targets of the National Poverty Reduction Strategy. It addresses the issues of agricultural taxation and fiscal aspects of the environment. The paper also focuses on a specific structural problem in taxation, and analyzes the fiscal aspects of environmental protection.